(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current practice of peripheral venous catheter (PVC) use, determine the incidence of phlebitis at the insertion site, and identify factors associated with peripheral venous phlebitis in patients. Subjects and Methods: The study was conducted on 340 inpatients treated at the Department of Neurology and Musculoskeletal Medicine, Can Tho City General Hospital in 2024, using a cross-sectional descriptive method. Data were collected using a pre-designed questionnaire Results: The most common PVC insertion sites were the dorsum of the hand 67.1% and forearm 27.4%, followed by the wrist 3.5% and antecubital fossa 1.8%. The incidence of phlebitis was 13.8%, of which grade 1 accounted for 12.9% and grade 2 for 0.9%. Factors associated with peripheral phlebitis included BMI, paralysis at the insertion site, alcohol abuse, smoking, history of venous thromboembolism, and reduced mobility. Conclusions: The incidence of peripheral venous phlebitis remains relatively high at 13.8%. Patients should limit alcohol consumption, avoid smoking, and increase physical activity. Nurses need to apply the new care protocols issued by the Ministry of Health to improve phlebitis outcomes in patients.